NANOSCALE INNOVATIONS: RECENT ADVANCES IN MATERIALS SCIENCE AND BIOMEDICAL APPLICATIONS OF NANOTECHNOLOGY - Vijay Kumar Valaboju (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Nanotechnology, the manipulation of matter at the atomic and molecular scale, has emerged as a transformative force in materials science and medicine. This article explores cutting-edge developments in nanomaterials and their applications across multiple sectors. We examine the properties and potential of carbon nanotubes and graphene in creating stronger, lighter materials for aerospace and electronics. The advent of self-healing materials and smart coatings, enabled by nanotechnology, promises to revolutionize construction and infrastructure maintenance. In the medical field, we analyze breakthroughs in targeted drug delivery systems, early disease detection using nanosensors, and the application of nanomaterials in regenerative medicine. The potential of nanorobotics in minimally invasive surgery and personalized medicine is also discussed. Furthermore, we explore future prospects in energy efficiency, environmental remediation, and consider the ethical implications of these advancing technologies. This comprehensive review underscores nanotechnology's pivotal role in addressing global challenges and its potential to reshape industries, while also highlighting the need for continued research into long-term safety and societal impacts.